(untitled) (2017)
This paper presents a study of the fluorescence quenching of 1-hydroxypyrene-3,6,8-trisulfonic acid (HPTS) in the presence of single-walled carbon nanotubes (SWCNT) using a fluorescence method. To investigate the quenching mechanism (dynamic or static) of HPTS, Stern-Volmer plots of single walled carbon nanotubes at different temperatures were used. The positive deviation from linearity in Stern-Volmer plots suggests that single walled carbon nanotubes follow a static quenching mechanism evidenced by the formation of a stable ground state complex. The results presented here help us to clarify the quenching mechanism in the interaction of a pyrene derived dye and carbon nanotubes. This study will open new possibilities in the use of the conjugate formed by SWCNTs and HPTS in the fabrication of abiosensor based on intracellular fluorescent probes.